A photosensitive resin ceramic composite material and its preparation method and application
By using a photosensitive resin ceramic composite material with a specific core-shell structure in ceramic photocuring printing, the coupling of coupling modified nanoceramic powder and photosensitive resin is solved, and the problem of insufficient density and poor curing performance of nanoceramic powder in photocuring printing is achieved, and higher density and photocuring performance are achieved.
Patent Information
- Application Number
- CN202411770007.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-04
AI Technical Summary
Nanoceramic powders have difficulties in preparing high-solid phase, low viscosity photocured ceramic slurries, insufficient density, gaps between particles, weak binding force, and high refractive index characteristics lead to poor curing performance.
The photosensitive resin ceramic composite material with a specific core-shell structure is adopted to form dense composite microspheres with the first photosensitive resin by coupling the modified nanoceramic powder, and the density and photocuring properties of the material are enhanced by the coating of the second photosensitive resin.
The tight bonding of nanoceramic powder is achieved, the density and photocuring performance of the material are improved, and the problems of insufficient density and poor curing performance in the prior art are solved.
Smart Images

Figure CN119241219B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic light-curing additive manufacturing, and in particular relates to a photosensitive resin ceramic composite material and a preparation method and application thereof. Background Art
[0002] As one of the most mature technologies in the field of ceramic additive manufacturing, ceramic photocuring printing technology has broad application prospects in many industries, especially in aerospace, automobile, machinery, power electronics, biomedicine, building materials and decorative materials. Its application market space is huge. Nano ceramic powder materials should be ideal raw materials for photocuring printing due to their high surface activity and excellent sintering activity. However, it is difficult for nano ceramic powder to prepare high solid phase and low viscosity photocuring ceramic slurry, which limits its direct application in ceramic photocuring printing. In order to apply nano ceramic powder to ceramic photocuring printing, nano ceramic powder can be formed into coarse agglomerates by agglomeration granulation to reduce its surface activity, so as to prepare a more ideal photocuring ceramic slurry. However, the current technical granulation has insufficient density of agglomerates, there are gaps between particles, the binding force is weak, and it is easy to break during the configuration process. In addition, many nano ceramic material systems often have poor curing performance due to their high refractive index characteristics, and it is difficult to achieve smooth printing even if they are prepared into slurry. Therefore, there is an urgent need for a technology that can effectively and tightly combine nano-ceramic powder particles and make the surface refractive index of the material system meet the requirements of ceramic photocuring printing. Summary of the invention
[0003] The present invention aims to improve at least one technical problem in the background technology.
[0004] In the first aspect, the present invention provides a photosensitive resin ceramic composite material, which includes an inner core and a shell layer, wherein the inner core includes a composite microsphere formed by a first material, the first material includes a coupled modified nano-ceramic powder and a first photosensitive resin, the coupled modified nano-ceramic powder is obtained by coupling modification of the nano-ceramic powder, and the coupling modification includes the following steps: mixing the nano-ceramic powder with water, adding a coupling agent, ball milling, and drying to obtain the coupled modified nano-ceramic powder; the shell layer includes a second photosensitive resin.
[0005] The present invention proposes a photosensitive resin ceramic composite material with a specific core-shell structure. In terms of the core, the first photosensitive resin in the present invention plays a bonding role. Through the photocuring of the first photosensitive resin, the nano-ceramic powder particles are tightly bonded together to form a high-density composite microsphere with a diameter of 1-10 microns. The realization of this dense granulation is due to the good compatibility between the coupled modified nano-ceramic powder and the first photosensitive resin. In terms of the shell layer, thanks to the compatibility between the first photosensitive resin of the core and the second photosensitive resin of the shell layer, the second photosensitive resin of the shell layer can completely cover the composite microsphere formed by the combination of the nano-ceramic particles in the core and the first photosensitive resin, further improving the density of the photosensitive resin ceramic composite material prepared by the present invention; in addition, the coating of the second photosensitive resin of the shell layer changes the optical properties of the surface of the coupled modified nano-ceramic powder, reduces its surface refractive index, and can effectively improve its photocuring performance.
[0006] Furthermore, the raw materials of the first material include: coupled modified nano-ceramic powder, a first photosensitive resin monomer and a first photoinitiator; the second photosensitive resin is formed by the second material, and the raw materials of the second material include: a second photosensitive resin monomer and a second photoinitiator.
[0007] Furthermore, by weight, the nano-ceramic powder is 100 parts, the coupling agent is 0.5-2 parts, the first photosensitive resin monomer is 5-30 parts, the first photoinitiator is 0.1-0.6 parts, the second photosensitive resin monomer is 2-5 parts, and the second photoinitiator is 0.04-0.1 parts.
[0008] Furthermore, the nano-ceramic powder is at least one of nano-alumina ceramic powder, nano-zirconia ceramic powder, nano-nickel oxide ceramic powder, nano-silicon carbide ceramic powder, nano-aluminum nitride ceramic powder and nano-silicon nitride ceramic powder; the coupling agent is at least one of methyl silane, epoxy silane, γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane and isopropoxydioleyloxy (dioctylphosphoyloxy) titanate; the first photosensitive resin monomer and the second photosensitive resin monomer are independently selected from at least one of 1,6-hexanediol diacrylate and 4,4',4''-trimethyltriphenylamine; the first photoinitiator and the second photoinitiator are independently selected from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.
[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned photosensitive resin ceramic composite material, comprising the following steps:
[0010] Conducting coupling modification on the nano-ceramic powder to obtain coupled modified nano-ceramic powder;
[0011] Dispersing the coupled modified nano-ceramic powder in the first anhydrous ethanol, adding the first photosensitive resin monomer and the first photoinitiator, and mixing well to obtain slurry A;
[0012] Dissolving the stabilizer in water to obtain slurry B;
[0013] Add slurry A dropwise into slurry B, and heat until the first anhydrous ethanol is completely evaporated to obtain slurry C;
[0014] Expose slurry C to ultraviolet light for the first time to cure the first photosensitive resin monomer to obtain slurry D;
[0015] Adding a second anhydrous ethanol, a second photosensitive resin monomer and a second photoinitiator to slurry D, heating until the second anhydrous ethanol is completely evaporated, and then irradiating with ultraviolet light for a second time to cure the second photosensitive resin monomer, to obtain slurry E;
[0016] The slurry E is subjected to hot filtration and hot water washing in sequence, the hot filtration temperature is 60°C-80°C, the hot water temperature is 60°C-80°C, and after hot filtration and hot water washing, it is dried to obtain a photosensitive resin ceramic composite material.
[0017] In the preparation method of the photosensitive resin ceramic composite material of the present invention, in order to realize the granulation of nano ceramic powder, the core lies in the use of evaporation organic phase emulsification technology. After the organic phase anhydrous ethanol is completely evaporated, the composite microspheres formed by the coupled modified nano ceramic powder and the first photosensitive resin form uniformly dispersed emulsified particles in the water solvent. The emulsified particles are freely suspended in the water phase. Thanks to the effect of surface tension, the composite microspheres are more tightly combined, and the sphericity is improved while the density is improved. When the first photosensitive resin is cured, due to the combined effect of the free suspension state and the surface tension, the first photosensitive resin can shrink freely, further strengthening the structure of the composite microspheres and improving the density. After the first photosensitive resin is completely cured, the present invention uses the second photosensitive resin to coat the previously formed composite microspheres by performing secondary emulsification and curing treatment, which not only further enhances the density of the material, but also reduces the surface refractive index of the coupled modified nano ceramic powder, and effectively improves the photocuring performance of the material.
[0018] The preparation method of the photosensitive resin ceramic composite material of the present invention also adopts a hot filtration and hot water washing method, which is beneficial to improving the dispersibility of the photosensitive resin ceramic composite material, preventing the powdered material from agglomerating into blocks, and avoiding the subsequent block crushing step from destroying the optical properties of the material surface.
[0019] Furthermore, in parts by weight, the nano-ceramic powder is 100 parts, the coupling agent is 0.5-2 parts, the first anhydrous ethanol is 80-120 parts, the first photosensitive resin monomer is 5-30 parts, the first photoinitiator is 0.1-0.6 parts, the second anhydrous ethanol is 5-10 parts, the second photosensitive resin monomer is 2-5 parts, and the second photoinitiator is 0.04-0.1 parts.
[0020] Furthermore, in slurry B, the mass ratio of stabilizer to water is (1-3): (500-1000); the stabilizer is polyvinyl pyrrolidone or polyvinyl alcohol.
[0021] Furthermore, the power of the first ultraviolet light irradiation and the second ultraviolet light irradiation is independently selected from 80W-120W, the curing time of the first photosensitive resin monomer is 30min-60min, and the curing time of the second photosensitive resin monomer is 1h-3h.
[0022] In a third aspect, the present invention provides an application of the above-mentioned photosensitive resin ceramic composite material in ceramic photocuring printing.
[0023] Beneficial effects of the invention: The invention combines evaporation organic phase emulsification technology, solidification technology and secondary emulsification and solidification technology to prepare a photosensitive resin ceramic composite material with a specific core-shell structure that has higher density and better sphericity than traditional granulation technology, and the obtained photosensitive resin ceramic composite material also exhibits better optical properties. The invention will help solve the current application problems of nano-ceramic powders in photocuring printing and further promote the development of technologies in related fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is an electronic photograph of the photosensitive resin ceramic composite material obtained in Example 1;
[0025] Figure 2 The present invention is a flow chart of the preparation method of the photosensitive resin ceramic composite material. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0027] The preparation process of photosensitive resin ceramic composite materials in the following content is as follows Figure 2 shown.
[0028] Example 1
[0029] A photosensitive resin ceramic composite material comprises raw materials by weight: 100 parts of nano zirconium oxide ceramic powder, 1.2 parts of gamma-glycidyloxypropyltrimethoxysilane, 21 parts of 1,6-hexanediol diacrylate, and 0.48 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0030] The preparation method is as follows:
[0031] 100 parts by weight of nano-zirconia ceramic powder was mixed with 100 parts by weight of water, 1.2 parts by weight of γ-glycidyloxypropyltrimethoxysilane was added, and the mixture was stirred and reacted in a water bath at 80° C. for 2 hours, and dried to obtain coupled modified nano-zirconia ceramic powder;
[0032] Dispersing the coupled modified nano-zirconia ceramic powder in 100 parts by weight of anhydrous ethanol, adding 18 parts by weight of 1,6-hexanediol diacrylate and 0.4 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and mixing well to obtain slurry A;
[0033] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0034] Slurry A was dripped into slurry B, and heated at 70°C until anhydrous ethanol was completely evaporated to obtain slurry C;
[0035] The slurry C was irradiated with ultraviolet light for 45 minutes using an ultraviolet lamp with a power of 100 W to cure the 1,6-hexanediol diacrylate to obtain slurry D;
[0036] Add 5 parts by weight of anhydrous ethanol, 3 parts by weight of 1,6-hexanediol diacrylate and 0.08 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide to slurry D, heat at 70° C. until the second anhydrous ethanol is completely evaporated, and then irradiate with ultraviolet light for 2 h using an ultraviolet lamp with a power of 100 W to cure the 1,6-hexanediol diacrylate to obtain slurry E;
[0037] The slurry E was heated to 60°C and then filtered. After filtering, the filter residue was washed 5 times with 80°C water, and then dried after washing 5 times to obtain a powdered photosensitive resin ceramic composite material. Its electronic photograph is as follows Figure 1 shown.
[0038] Example 2
[0039] A photosensitive resin ceramic composite material comprises raw materials by weight: 100 parts of nano zirconium oxide ceramic powder, 0.8 parts of gamma-glycidyloxypropyltrimethoxysilane, 17 parts of 1,6-hexanediol diacrylate, and 0.3 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0040] The preparation method is as follows:
[0041] 100 parts by weight of nano-zirconia ceramic powder was mixed with 100 parts by weight of water, 0.8 parts by weight of γ-glycidyloxypropyltrimethoxysilane was added, and the mixture was stirred and reacted in a water bath at 80° C. for 2 hours, and dried to obtain coupled modified nano-zirconia ceramic powder;
[0042] Dispersing the coupled modified nano-zirconia ceramic powder in 100 parts by weight of anhydrous ethanol, adding 12 parts by weight of 1,6-hexanediol diacrylate and 0.2 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and mixing well to obtain slurry A;
[0043] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0044] Slurry A was dripped into slurry B, and heated at 70°C until anhydrous ethanol was completely evaporated to obtain slurry C;
[0045] The slurry C was irradiated with ultraviolet light for 35 minutes using an ultraviolet lamp with a power of 100 W to cure the 1,6-hexanediol diacrylate to obtain slurry D;
[0046] Add 5 parts by weight of anhydrous ethanol, 5 parts by weight of 1,6-hexanediol diacrylate and 0.1 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide to slurry D, heat at 70° C. until the second anhydrous ethanol is completely evaporated, and then irradiate with ultraviolet light for 3 hours using an ultraviolet lamp with a power of 100 W to cure the 1,6-hexanediol diacrylate to obtain slurry E;
[0047] The slurry E was heated to 60° C. and then filtered. After filtering, the filter residue was washed 5 times with 80° C. water, and then dried after washing 5 times to obtain a powdery photosensitive resin ceramic composite material.
[0048] Example 3
[0049] A photosensitive resin ceramic composite material comprises raw materials by weight: 100 parts of nano zirconium oxide ceramic powder, 2 parts of gamma-glycidyloxypropyltrimethoxysilane, 29 parts of 1,6-hexanediol diacrylate, and 0.64 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0050] The preparation method is as follows:
[0051] 100 parts by weight of nano-zirconia ceramic powder was mixed with 100 parts by weight of water, 2 parts by weight of γ-glycidyloxypropyltrimethoxysilane was added, and the mixture was stirred and reacted in a water bath at 80° C. for 2 hours, and dried to obtain coupled modified nano-zirconia ceramic powder;
[0052] Dispersing the coupled modified nano-zirconia ceramic powder in 100 parts by weight of anhydrous ethanol, adding 27 parts by weight of 1,6-hexanediol diacrylate and 0.6 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and mixing well to obtain slurry A;
[0053] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0054] Slurry A was dripped into slurry B, and heated at 70°C until anhydrous ethanol was completely evaporated to obtain slurry C;
[0055] The slurry C was irradiated with ultraviolet light for 60 minutes using an ultraviolet lamp with a power of 100 W to cure the 1,6-hexanediol diacrylate to obtain slurry D;
[0056] 5 parts by weight of anhydrous ethanol, 2 parts by weight of 1,6-hexanediol diacrylate and 0.04 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide were added to slurry D, and the mixture was heated at 70° C. until the second anhydrous ethanol was completely evaporated, and then irradiated with ultraviolet light for 1 h using an ultraviolet lamp with a power of 100 W to cure the 1,6-hexanediol diacrylate, to obtain slurry E;
[0057] The slurry E was heated to 60° C. and then filtered. After filtering, the filter residue was washed 5 times with 80° C. water, and then dried after washing 5 times to obtain a powdery photosensitive resin ceramic composite material.
[0058] Example 4
[0059] A photosensitive resin ceramic composite material comprises the following raw materials by weight: 100 parts of nano silicon carbide ceramic powder, 1 part of methyl silane, 24 parts of 4,4',4''-trimethyltriphenylamine, and 0.48 parts of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.
[0060] The preparation method is as follows:
[0061] 100 parts by weight of nano silicon carbide ceramic powder was mixed with 150 parts by weight of water, 1 part by weight of methylsilane was added, and the mixture was stirred and reacted in a water bath at 80° C. for 2 hours, and dried to obtain a coupled modified nano silicon carbide ceramic powder;
[0062] Dispersing the coupled modified nano silicon carbide ceramic powder in 100 parts by weight of anhydrous ethanol, adding 20 parts by weight of 4,4',4''-trimethyltriphenylamine and 0.4 parts by weight of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and mixing well to obtain slurry A;
[0063] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0064] Slurry A was dripped into slurry B, and heated at 65°C until anhydrous ethanol was completely evaporated to obtain slurry C;
[0065] The slurry C was irradiated with ultraviolet light for 50 minutes using an ultraviolet lamp with a power of 90 W to solidify the 4,4',4''-trimethyltriphenylamine to obtain slurry D;
[0066] 5 parts by weight of anhydrous ethanol, 4 parts by weight of 4,4',4''-trimethyltriphenylamine and 0.08 parts by weight of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide were added to slurry D, and the mixture was heated at 65° C. until the second anhydrous ethanol was completely evaporated, and then irradiated with ultraviolet light for 3 h using an ultraviolet lamp with a power of 110 W to solidify the 4,4',4''-trimethyltriphenylamine to obtain slurry E;
[0067] The slurry E was heated to 80° C. and then filtered. After filtering, the filter residue was washed 5 times with 60° C. water, and then dried after washing 5 times to obtain a powdery photosensitive resin ceramic composite material.
[0068] Example 5
[0069] A photosensitive resin ceramic composite material, whose raw materials include, by weight: 100 parts of nano silicon carbide ceramic powder, 1 part of isopropoxy dioleyl (dioctyl phosphate) titanate, 21 parts of 4,4',4''-trimethyl triphenylamine, and 0.37 parts of bis(2,4,6-trimethylbenzoyl)phenyl phosphine oxide.
[0070] The preparation method is as follows:
[0071] 100 parts by weight of nano silicon carbide ceramic powder was mixed with 120 parts by weight of water, 1 part by weight of isopropoxy dioleyl (dioctyl phosphate) titanate was added, and the mixture was stirred and reacted in a water bath at 80° C. for 2 h, and dried to obtain a coupled modified nano silicon carbide ceramic powder;
[0072] Dispersing the coupled modified nano silicon carbide ceramic powder in 100 parts by weight of anhydrous ethanol, adding 18 parts by weight of 4,4',4''-trimethyltriphenylamine and 0.3 parts by weight of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, and mixing well to obtain slurry A;
[0073] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0074] Slurry A was dripped into slurry B, and heated at 65°C until anhydrous ethanol was completely evaporated to obtain slurry C;
[0075] The slurry C was irradiated with ultraviolet light for 45 minutes using an ultraviolet lamp with a power of 120 W to solidify the 4,4',4''-trimethyltriphenylamine to obtain slurry D;
[0076] 5 parts by weight of anhydrous ethanol, 3 parts by weight of 4,4',4''-trimethyltriphenylamine and 0.07 parts by weight of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide were added to slurry D, and the mixture was heated at 65° C. until the second anhydrous ethanol was completely evaporated, and then irradiated with ultraviolet light for 2 h using an ultraviolet lamp with a power of 80 W to solidify the 4,4',4''-trimethyltriphenylamine to obtain slurry E;
[0077] The slurry E was heated to 70° C. and then filtered. After filtering, the filter residue was washed 5 times with 70° C. water, and then dried after washing 5 times to obtain a powdery photosensitive resin ceramic composite material.
[0078] Comparative Example 1
[0079] A nano ceramic material, whose raw materials include, by weight: 100 parts of nano zirconium oxide ceramic powder, 21 parts of 1,6-hexanediol diacrylate, and 0.48 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0080] The preparation method is as follows:
[0081] Dispersing nano zirconium oxide ceramic powder in 100 parts by weight of anhydrous ethanol, adding 18 parts by weight of 1,6-hexanediol diacrylate and 0.4 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and mixing well to obtain slurry A;
[0082] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0083] Slurry A was dripped into slurry B, and heated at 70°C until anhydrous ethanol was completely evaporated to obtain slurry C;
[0084] The slurry C was irradiated with ultraviolet light for 45 minutes using an ultraviolet lamp with a power of 100 W to cure the 1,6-hexanediol diacrylate to obtain slurry D;
[0085] Add 5 parts by weight of anhydrous ethanol, 3 parts by weight of 1,6-hexanediol diacrylate and 0.08 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide to slurry D, heat at 70° C. until the second anhydrous ethanol is completely evaporated, and then irradiate with ultraviolet light for 2 h using an ultraviolet lamp with a power of 100 W to cure the 1,6-hexanediol diacrylate to obtain slurry E;
[0086] The slurry E was heated to 60° C. and then filtered. After filtering, the filter residue was rinsed 5 times with 80° C. water, and then dried to obtain a nano-ceramic material.
[0087] Comparative Example 2
[0088] A nano ceramic material, whose raw materials include, by weight: 100 parts of nano zirconium oxide ceramic powder, 1.2 parts of gamma-glycidyloxypropyltrimethoxysilane, 21 parts of 1,6-hexanediol diacrylate, and 0.48 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0089] The preparation method is as follows:
[0090] 100 parts by weight of nano-zirconia ceramic powder was mixed with 100 parts by weight of water, 1.2 parts by weight of γ-glycidyloxypropyltrimethoxysilane was added, and the mixture was stirred and reacted in a water bath at 80° C. for 2 hours, and dried to obtain coupled modified nano-zirconia ceramic powder;
[0091] Dispersing the coupled modified nano-zirconia ceramic powder in 100 parts by weight of water, adding 18 parts by weight of 1,6-hexanediol diacrylate and 0.4 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and mixing well to obtain slurry A;
[0092] Dissolve 1 part by weight of polyvinyl pyrrolidone in 700 parts by weight of water to obtain slurry B;
[0093] Add slurry A dropwise into slurry B and mix well to obtain slurry C;
[0094] The slurry C was irradiated with ultraviolet light for 45 minutes using an ultraviolet lamp with a power of 100 W to cure the 1,6-hexanediol diacrylate to obtain slurry D;
[0095] 3 parts by weight of 1,6-hexanediol diacrylate and 0.08 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide were added to slurry D, and the mixture was mixed, and then irradiated with ultraviolet light for 2 hours using an ultraviolet lamp with a power of 100 W to cure the 1,6-hexanediol diacrylate to obtain slurry E;
[0096] The slurry E was heated to 60° C. and then filtered. After filtering, the filter residue was rinsed 5 times with 80° C. water, and then dried to obtain a nano-ceramic material.
[0097] Comparative Example 3
[0098] A nano ceramic material, whose raw materials include, by weight: 100 parts of nano zirconium oxide ceramic powder, 1.2 parts of gamma-glycidyloxypropyltrimethoxysilane, 18 parts of 1,6-hexanediol diacrylate, and 0.4 parts of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0099] The preparation method is as follows:
[0100] 100 parts by weight of nano-zirconia ceramic powder was mixed with 100 parts by weight of water, 1.2 parts by weight of γ-glycidyloxypropyltrimethoxysilane was added, and the mixture was stirred and reacted in a water bath at 80° C. for 2 hours, and dried to obtain coupled modified nano-zirconia ceramic powder;
[0101] Dispersing the coupled modified nano-zirconia ceramic powder in 100 parts by weight of anhydrous ethanol, adding 18 parts by weight of 1,6-hexanediol diacrylate and 0.4 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and mixing well to obtain slurry A;
[0102] Dissolve 1 part by weight of polyvinyl pyrrolidone in 800 parts by weight of water to obtain slurry B;
[0103] Slurry A was dripped into slurry B, and heated at 70°C until anhydrous ethanol was completely evaporated to obtain slurry C;
[0104] The slurry C was irradiated with ultraviolet light for 45 minutes using an ultraviolet lamp with a power of 100 W to cure the 1,6-hexanediol diacrylate to obtain slurry D;
[0105] The slurry D was heated to 60° C. and then filtered. After filtering, the filter residue was rinsed 5 times with 80° C. water, and then dried to obtain a nano-ceramic material.
[0106] Comparative Example 4
[0107] Nano-zirconia ceramic powder without any treatment is used as the nano-ceramic material.
[0108] The testing methods and steps for the relevant performance of the products in the examples and comparative examples of the present application are as follows:
[0109] 1. Preparation of light-cured ceramic slurry
[0110] 100 parts by weight of the product, 20 parts by weight of trimethylolpropane trimethacrylate (photosensitive resin), 8 parts by weight of sodium ethylenediaminetetraacetate (dispersant) and 2 parts by weight of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (photoinitiator) were ball-milled and mixed for 5 hours to obtain a photocurable ceramic slurry. In order to facilitate the control of variables for comparison, the solid content of the photocurable ceramic slurry should be kept as close as possible during the preparation of the slurry in the evaluation.
[0111] 2. Calculation of solid content of light-cured ceramic slurry
[0112] The solid content of the photocurable ceramic slurry is calculated by the following formula:
[0113]
[0114] Where m fis the product mass, m1 is the photosensitive resin mass, m2 is the dispersant mass, and m3 is the photoinitiator mass.
[0115] 3. Evaluation of light-cured ceramic slurry
[0116] The slurry flow state is visually evaluated and divided into five levels: poor, poor, fair, good, and good.
[0117] 4. Viscosity test of light-cured ceramic slurry
[0118] The viscosity of the photocurable ceramic slurry was measured using a Fungilab Viscolead Adv R rotational viscometer.
[0119] 5. Evaluation of curing effect of light-cured ceramic slurry
[0120] Use a light-curing ceramic slurry to cure a single layer for 5 seconds on a light-curing machine, perform single-layer curing characterization, measure the curing depth, and evaluate the curing effect.
[0121] The relevant test results are shown in Table 1.
[0122] Table 1 Test results of Example 1 and Comparative Examples 1-5
[0123]
[0124] Compared with Example 1, the nano-zirconia ceramic powder in Comparative Example 1 has not undergone coupling modification, and the composite rate of the nano-zirconia ceramic powder that has not been coupled modified and the photosensitive resin is not good. There may be local incompatibility between the powder and the resin, that is, the specific core-shell structure of the present invention cannot be formed, the optical properties of the surface of the nano-zirconia ceramic powder are not well improved, and the curing effect is not ideal.
[0125] Compared with Example 1, Comparative Example 2 does not use the organic phase evaporation emulsification technology during the preparation process, and the slurry state of Comparative Example 2 is poor. Because the organic phase evaporation emulsification technology is not used, the nano-zirconia ceramic powder and the photosensitive resin are difficult to freely form balls in the water phase and cannot be tightly combined, resulting in the final material being not dense and difficult to prepare a high-solid content, low-viscosity photocurable ceramic slurry.
[0126] Compared with Example 1, Comparative Example 3 does not undergo secondary emulsification and curing during the preparation process. However, after organic phase evaporation, emulsification and curing in the preparation process, the material of Comparative Example 3 has a certain density and can be used to prepare a high-solid content, low-viscosity photocurable ceramic slurry. By comparing the curing depth, it can be seen that Example 1 has a better printing effect, indicating that the optical properties of the surface of the nano-zirconia ceramic powder are better improved after secondary emulsification and curing.
[0127] Compared with Example 1, Comparative Example 4 is a nano-zirconia ceramic powder that has not undergone any modification. It can be seen that the nano-zirconia ceramic powder that has not undergone any modification is difficult to prepare a high-solid content photocurable ceramic slurry and cannot be directly used in ceramic photocuring printing.
[0128] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.
Claims
1. A photosensitive resin ceramic composite material, characterized in that: The photosensitive resin ceramic composite material comprises a core and a shell, wherein the core comprises composite microspheres formed of a first material; The raw materials of the first material include: coupled modified nano-ceramic powder, a first photosensitive resin monomer and a first photoinitiator; The coupling-modified nano-ceramic powder is obtained by coupling-modifying the nano-ceramic powder, and the coupling-modification comprises the following steps: mixing the nano-ceramic powder with water, adding a coupling agent, ball-milling, and drying to obtain the coupling-modified nano-ceramic powder; The shell layer includes a second photosensitive resin, the second photosensitive resin is formed of a second material, and the raw materials of the second material include: a second photosensitive resin monomer and a second photoinitiator; The preparation method of the photosensitive resin ceramic composite material comprises the following steps: Dispersing the coupled modified nano-ceramic powder in the first anhydrous ethanol, adding the first photosensitive resin monomer and the first photoinitiator, and mixing well to obtain slurry A; Dissolving the stabilizer in water to obtain slurry B; The slurry A is dripped into the slurry B, and heated until the first anhydrous ethanol is completely evaporated to obtain slurry C; irradiating the slurry C with ultraviolet light for the first time to cure the first photosensitive resin monomer to obtain slurry D; Adding a second anhydrous ethanol, the second photosensitive resin monomer and the second photoinitiator to the slurry D, heating until the second anhydrous ethanol is completely evaporated, and then irradiating with ultraviolet light for a second time to cure the second photosensitive resin monomer, to obtain slurry E; The slurry E is sequentially subjected to hot filtration and hot water washing, wherein the temperature of the hot filtration is 60° C.-80° C., the temperature of the hot water is 60° C.-80° C., and then dried to obtain the photosensitive resin ceramic composite material.
2. The photosensitive resin ceramic composite material according to claim 1, characterized in that: In parts by weight, the nano-ceramic powder is 100 parts, the coupling agent is 0.5-2 parts, the first photosensitive resin monomer is 5-30 parts, the first photoinitiator is 0.1-0.6 parts, the second photosensitive resin monomer is 2-5 parts, and the second photoinitiator is 0.04-0.1 parts.
3. The photosensitive resin ceramic composite material according to claim 1, characterized in that: The nano ceramic powder is at least one of nano alumina ceramic powder, nano zirconium oxide ceramic powder, nano nickel oxide ceramic powder, nano silicon carbide ceramic powder, nano aluminum nitride ceramic powder and nano silicon nitride ceramic powder; and / or, the coupling agent is at least one of methyl silane, epoxy silane, γ-glycidyloxypropyl trimethoxy silane, γ-aminopropyl triethoxy silane and isopropoxy dioleyloxy (dioctyl phosphate acyloxy) titanate; and / or, the first photosensitive resin monomer and the second photosensitive resin monomer are independently selected from at least one of 1,6-hexanediol diacrylate and 4,4',4''-trimethyltriphenylamine; and / or, the first photoinitiator and the second photoinitiator are independently selected from at least one of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.
4. The photosensitive resin ceramic composite material according to claim 1, characterized in that: The diameter of the composite microspheres is 1-10 microns.
5. A method for preparing the photosensitive resin ceramic composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Performing the coupling modification on the nano-ceramic powder to obtain the coupling modified nano-ceramic powder; Dispersing the coupled modified nano-ceramic powder in the first anhydrous ethanol, adding the first photosensitive resin monomer and the first photoinitiator, and mixing well to obtain slurry A; Dissolving the stabilizer in water to obtain slurry B; The slurry A is dripped into the slurry B, and heated until the first anhydrous ethanol is completely evaporated to obtain slurry C; irradiating the slurry C with ultraviolet light for the first time to cure the first photosensitive resin monomer to obtain slurry D; Adding a second anhydrous ethanol, the second photosensitive resin monomer and the second photoinitiator to the slurry D, heating until the second anhydrous ethanol is completely evaporated, and then irradiating with ultraviolet light for a second time to cure the second photosensitive resin monomer, to obtain slurry E; The slurry E is sequentially subjected to hot filtration and hot water washing, wherein the temperature of the hot filtration is 60° C.-80° C., the temperature of the hot water is 60° C.-80° C., and then dried to obtain the photosensitive resin ceramic composite material.
6. The method for preparing a photosensitive resin ceramic composite material according to claim 5, characterized in that: In parts by weight, the nano-ceramic powder is 100 parts, the coupling agent is 0.5-2 parts, the first anhydrous ethanol is 80-120 parts, the first photosensitive resin monomer is 5-30 parts, the first photoinitiator is 0.1-0.6 parts, the second anhydrous ethanol is 5-10 parts, the second photosensitive resin monomer is 2-5 parts, and the second photoinitiator is 0.04-0.1 parts.
7. The method for preparing a photosensitive resin ceramic composite material according to claim 5, characterized in that: In the slurry B, the mass ratio of the stabilizer to water is (1-3): (500-1000); and / or, the stabilizer is polyvinyl pyrrolidone or polyvinyl alcohol.
8. The method for preparing a photosensitive resin ceramic composite material according to claim 5, characterized in that: The powers of the first ultraviolet light irradiation and the second ultraviolet light irradiation are independently selected from 80W-120W, the curing time of the first photosensitive resin monomer is 30min-60min, and the curing time of the second photosensitive resin monomer is 1h-3h.
9. Use of the photosensitive resin ceramic composite material according to any one of claims 1 to 4 in ceramic photocuring printing.
Citation Information
Patent Citations
Purple sand ceramic slurry suitable for photocuring additive manufacturing and preparation method of purple sand ceramic slurry
CN118184302A
Ceramic slurry for photocuring forming of artificial bone scaffold and preparation method of ceramic slurry
CN118359428A
Titanium dioxide / polymer hollow microspheres and heat-insulating coating prepared from titanium dioxide / polymer hollow microspheres
CN118702880A